Simulation of Outer Rotor Permanent Magnet Brushless DC Motor Using Finite Element Method for Torque Improvement. (8th August 2012) - Kumaravelu, Uma Devi; Mohamed Yakub, Sanavullah
Abstract : A method of simulation and modeling outer rotor permanent magnet brushless DC (ORPMBLDC) motor under dynamic conditions using finite element method by FEMM 4.2 software package is presented. In the proposed simulation, the torque developed at various positions of the rotor, under a complete cycle of excitation of the stator, is analysed. A novel method of sinusoidal excitation is proposed to enhance the overall torque development of ORPMBLDC motor.